The patatin-like phospholipase PfPNPLA2 is involved in the mitochondrial degradation of phosphatidylglycerol during Plasmodium falciparum blood stage development - Shunmugam, Serena; Quansah, Nyamekye; Flammersfeld, Ansgar; Islam, Md Muzahidul; Sassmannshausen, Juliane; Bennink, Sandra; Yamaryo-Botté, Yoshiki; Pradel, Gabriele; Botté, Cyrille Y. (Frontiers in Cellular and Infection Microbiology, 2023)
Plasmodium falciparum is an Apicomplexa responsible for human malaria, a major disease causing more than ½ million deaths every year, against which there is no fully efficient vaccine. The current rapid emergence of drug resistances emphasizes the need to identify novel drug targets. Increasing evidences show that lipid synthesis and trafficking are essential for parasite survival and pathogenesis, and that these pathways represent potential points of attack. Large amounts of phospholipids are needed for the generation of membrane compartments for newly divided parasites in the host cell. Parasite membrane homeostasis is achieved by an essential combination of parasite de novo lipid synthesis/recycling and massive host lipid scavenging. Latest data suggest that the mobilization and channeling of lipid resources is key for asexual parasite survival within the host red blood cell, but the molecular actors allowing lipid acquisition are poorly characterized. Enzymes remodeling lipids such as phospholipases are likely involved in these mechanisms. P. falciparum possesses an unusually large set of phospholipases, whose functions are largely unknown. Here we focused on the putative patatin-like phospholipase PfPNPLA2, for which we generated an glmS-inducible knockdown line and investigated its role during blood stages malaria. Disruption of the mitochondrial PfPNPLA2 in the asexual blood stages affected mitochondrial morphology and further induced a significant defect in parasite replication and survival, in particular under low host lipid availability. Lipidomic analyses revealed that PfPNPLA2 specifically degrades the parasite membrane lipid phosphatidylglycerol to generate lysobisphosphatidic acid. PfPNPLA2 knockdown further resulted in an increased host lipid scavenging accumulating in the form of storage lipids and free fatty acids. These results suggest that PfPNPLA2 is involved in the recycling of parasite phosphatidylglycerol to sustain optimal intraerythrocytic development when the host resources are scarce. This work strengthens our understanding of the complex lipid homeostasis pathways to acquire lipids and allow asexual parasite survival.